Pengembangan microlearning dalam MOOC untuk pendidikan ilmu komputer - Hasmidarahma Hasmidarahma; Nurhikmah H; Farida Febriati (Curricula: Journal of Curriculum Development, 2026)
Students' difficulties in learning computer science can hinder their ability to master skills in the industrial world. Therefore, this study aims to develop microlearning for Massive Open Online Courses (MOOCs) in computer science subjects using the Edukati platform. The development methods used include the ADDIE model, the 4D (Four-D) model, and Dick and Carey. The research was conducted at SMK Negeri 1 Makassar, involving 34 students, 1 computer science teacher, and 2 validators (subject-matter and media experts) as subjects. Data were collected through a needs questionnaire, expert validation, user responses, and pretest and posttest. The results of the needs analysis showed that students had difficulty understanding the material in conventional formats but showed a strong interest in digital video-based learning. The design process included compiling material in accordance with the curriculum and producing videos using Canva and CapCut, which were then integrated into Edukati. Expert validation demonstrated very high validity, while trials showed good practicality. Effectiveness tests showed a significant improvement in student learning outcomes. Thus, microlearning in MOOCs has been proven to be valid, practical, and effective as an innovative solution for learning Informatics in vocational schools.